Penafsiran Eskatologi Wujudi Mulla Sadra: Makna Filosofis Peristiwa Eskatologi dalam Surah al-Zilzal - Fadel, Achmad; Adnani, Hasyim; Gama, Cipta Bakti Gama; Syam, Muhammad Asrul; Achmad Fadel (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2024)
This research This research aims to analyze the eschatological phenomenon in Surah Al-Zalzalah based on the approach of Mulla Sadra's Philosophy of Existence. The eschatological phenomenon described in the Qur'an is an event that can be believed not only through dogmatic methods but also through rational-speculative means. The focus of the events to be discussed here is the Day of Judgment, resurrection (sudur an-nas), and recompense (jaza’). These three events go beyond sensory instruments and scientific testing, making them philosophical issues that are suitable to be understood within a rational-universal framework. Mulla Sadra offers a rational explanation based on the Transcendental Theosophy theory (al-Hikmah al-Muta’aliyyah) to understand the events of the Day of Judgment, resurrection, and recompense. The source of data is taken from Tafsir al-Qur'an al-Karim by Sadra, edited by Khajavi. This research involves a literature review using the Philosophy of Existence theory by Sadra. The results of this study indicate that each eschatological phenomenon is a form of evolution and modulation of existence. Firstly, the Day of Judgment is interpreted as the process of actualization and perfection of material, where the Earth is replaced by another Earth, and every substance undergoes a perfecting movement. Resurrection is the actualization of every potential and the forms of souls toward the original form of each creature. Recompense is the original psychological form of the soul when resurrected, producing either happiness or misery. This interpretation implies a more Sufi approach to religion, attributing every goodness or badness to the condition of the individual soul's form